Didactics of Biology — Development and Current State - Dostál, Petr (Scientia in educatione, 2013)
The paper describes the foundation and development of didactics of biology in our country from post-war years to nowadays. It pays attention to the key figures in this field and important landmarks of its development. However, it also highlights some problems which exist in contemporary didactics of biology as a science. The paper discusses the cooperation of the Faculty of Education and Faculty of Sciences at Charles University in Prague in the field of biology. A survey of university textbooks and lecture notes of didactics of biology which have been published in our country since 1945 is given.